Valorization of Bitter Gourd (Momordica charantia) Seeds as a Functional Food Ingredient: Physicochemical and Structural Characterization - Radha Ranganathan; Bhawaani Selvakumar; Tinu Dhanaraj (Agro Bali : Agricultural Journal, 2026)
Bitter gourd (Momordica charantia) seeds are commonly discarded as agro-industrial by-products despite their rich nutritional composition and potential as functional food ingredients. The underutilization of these seeds not only contributes to environmental burdens but also represents a missed opportunity for sustainable waste valorization and resource recovery. Although increasing attention has been paid to the utilization of food processing by-products, limited information is available on the effects of lyophilization on the physicochemical, functional, structural, thermal, and morphological properties of bitter gourd seed powder. Therefore, this study aimed to compare untreated bitter gourd seed powder (BGSP) with lyophilized bitter gourd seed powder (LBGSP) to determine the effectiveness of lyophilization in preserving and enhancing the quality attributes of the resulting powder for potential functional food applications. Functional properties, including the water absorption index, oil absorption index, wettability, and swelling index, were determined using standardized analytical methods. Structural and morphological characteristics were investigated using Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), field-emission scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (FESEM–EDX), dynamic light scattering (DLS), and zeta potential analyses. Compared with untreated BGSP, LBGSP exhibited superior functional performance, improved preservation of proteins, polysaccharides, and other functional groups, a more porous and less aggregated microstructure, greater retention of essential mineral elements, enhanced colloidal stability, and reduced particle aggregation. Furthermore, thermal analysis revealed a substantially higher residual mass for LBGSP (23.1%) than for BGSP (11.42%), indicating improved thermal stability. These improvements were primarily attributed to the low-temperature vacuum dehydration process during lyophilization, which effectively minimized thermal degradation while preserving structural integrity and biofunctional components. Overall, the findings demonstrate that lyophilization is an effective processing strategy for improving the functional and structural quality of bitter gourd seed powder, thereby supporting its development as a sustainable functional food ingredient while promoting the valorization of agro-industrial waste.